An ultrahigh dielectric constant composite based on polyvinylidene fluoride and polyethylene glycol modified ferroferric oxide. (5th August 2015) - Zhu, Jiujun; Li, Weiping; Huo, Xiaoyun; Li, Lili; Li, Ya; Luo, Laihui; Zhu, Yuejin
Abstract: To improve the compatibility between a filler and polymer matrix, a polyethylene glycol (PEG) surface modifier was used for modification in the polyvinylidene fluoride (PVDF) and ferroferric oxide (Fe3 O4 ) composites. It is found that the PEG-modified Fe3 O4 and PVDF composites have a much higher dielectric constant and better suppressed dielectric loss than the other similar percolative systems. The maximum of the dielectric constant can be up to 63 000 while the dielectric loss is controlled below 4.5. Finally, the microscopic reasons for this improvement are presented. It is helpful to understand the influence of surface modification agents on the interfaces between the filler and matrix.